THE INDICATOR OF EMPLOYMENT PROTECTION LEGISLATION FOR CANADA - Amine, Samir; Montreuil, Véra-Line (The European Journal of Applied Economics, 2018)
Since the early 1990s, employment protection legislation (EPL) has becomea concern for public policy makers in particular with respect to itsimpact on unemployment and productivity. This topic arose pronouncedattention of international organizations. Indeed, these institutions havebuilt analytical models to assess the strictness of EPL in different countries,but we find that these models are sometimes incomplete despitethe abundance of information they provide. The purpose of this articleis to propose the introduction of new elements to the Organization forEconomic Co-operation and Development (OECD) analysis model basedon the Canadian experience. We, thus, propose to adjust the syntheticindicator of EPL for Canada taking into account local specificities nottaken into consideration by the OECD.